Rancangan Program Pengembagan Mengelola Emosi (Self Regulation) Berbasis Teknologi Informasi sebagai Salah Satu Upaya Penerapan Revolusi Industri 4.0 - Atisyatul Aini; Helma Helma; Mori Dianto (Universitas PGRI SUMATERA BARAT, 2021)
ABSTRACT This research is motivated by the phenomenon of students who have not been able to understand the ability to manage emotions, are less concerned when the teaching and learning process takes place, are easy to develop emotions with friends, and there is no special service program design for the emotional development of students based on information technology. The purpose of the study was to reveal the ability of students to manage emotions and to design Guidance and Counseling service programs based on Information Technology according to the problems of students at the State Vocational High School 1 Sintuk Toboh Gadang related to the ability to manage emotions. This type of research used quantitative descriptive method. The population of this study was students in class XI TBSMi State Vocational High School 1 Sintuk Toboh Gadang. Sampling in this study used a total sampling technique, where researchers took the entire population of 64 respondents. The instrument used in this research is a questionnaire. To analyze the data, the percentage and mean formulas were used. The application that the researcher designed has been validated by 3 theoretical experts, 1 practitioner expert and 1 media expert, namely by obtaining a total expert score of 3.36 with the